Adolescent Pregnancy and its Outcome in a Rural Teaching Hospital, Karnali Academy of Health Science, Jumla - Rai, Purnima; Sindan, Namrata; Acharya, Bishnu Dutta; Shah, Rajiv; Shrestha, Sandeep (Journal of Karnali Academy of Health Sciences, 2019)
Introduction: Nepal is a low socioeconomic country and adolescent pregnancy can have deleterious effects on health as well as social wellbeing of the mother, child and the community. The aim of this study was to find the frequency of teenage pregnancy and its outcomes in Karnali Academy of Health Science.Method: This was a retrospective study conducted in Karnali Academy of Health Science, Jumla, Nepal. Data was collected from the hospital records from October 2017 to September 2018.Result: The frequency of teenage pregnancy was 22.6% among total deliveries. Most of them were primigravida (84.9%). Majority of them were 18 years of age (47.5%). Caesarean section accounted for 10.8%. In perinatal outcome, the incidence of preterm birth was 15.1%, and extremely low birth weight was 2.2%, very low birth weight was 1.4% and low birth weight was 12.2%. Maternal complication accounted for 33.09%.Conclusion: The study concluded that frequency of teenage pregnancy is considerably high and it is associated with increases risk of adverse outcome to both mother and newborn such as intrauterine fetal death, retained placenta, and malpresentations. Therefore, education and awareness can be helpful in reducing adolescent pregnancy and its adverse outcomes.